Vì n^2 + 4 * n+1 => n(n+1) - (n+1) +5 * n+1 => 5 * n+1 => n+1 thuộc 1;5 => n=0 hoặc n=4
n2 + 4 chia hết ho n + 1
n(n + 1) chia hết cho n + 1
n2 + n chia hết cho n + 1
< = > [(n2 + n)-(n2 + 4)] chia hết cho n + 1
< = > (n2 + n - n2 - 4) chia hết cho n + 1
n - 4 chia hết cho n + 1
n + 1 - 5 chia hết cho n + 1
Mà n + 1 chia hết cho n + 1
< = > 5 chia hết cho n +1
n + 1 thuộc U(5) = {-5;-1;1;5}
n + 1 = -5 => n = -6
n + 1 = -1 => n = -2
n +1 = 1 => n = 0
n + 1 = 5 => n = 4
Mà n thuộc N*
Do đó n = 4
tui giải đại đại
n2 + 4 chia hết cho n + 1
4 - 1 = 3
mà 32 = 9
9 - (4 + 1) = 4
n = 4